2007
DOI: 10.1667/rr0802.1
|View full text |Cite
|
Sign up to set email alerts
|

In VitroStudy of the Stress Response of Human Skin Cells to GSM-1800 Mobile Phone Signals Compared to UVB Radiation and Heat Shock

Abstract: The evolution of mobile phone technology is toward an increase of the carrier frequency up to 2.45 GHz. Absorption of radiofrequency (RF) radiation becomes more superficial as the frequency increases. This increasingly superficial absorption of RF radiation by the skin, which is the first organ exposed to RF radiation, may lead to stress responses in skin cells. We thus investigated the expression of three heat-shock proteins (HSP70, HSC70, HSP27) using immunohistochemistry and induction of apoptosis by flow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 72 publications
1
21
0
Order By: Relevance
“…In vitro studies, carried out on different cell systems, have yielded different results, indicating that cell sensitivity to electromagnetic fields may differ according to the cell type. For example, Hsp expression is not changed in fibroblasts and keratinocytes [24] , peripheral blood mononuclear cells [25] and neuroblastoma cell line SK-N-SH exposed to RF/MW at low SAR levels [5] . Howeer, Hsp expression has been reported to be upregulated by RF/electromagnetic field exposure in KB cells [26] , and levels of the inducible Hsp70C transcript were significantly enhanced after 24 h exposure to GSM signals in human trophoblast cells [27] .…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies, carried out on different cell systems, have yielded different results, indicating that cell sensitivity to electromagnetic fields may differ according to the cell type. For example, Hsp expression is not changed in fibroblasts and keratinocytes [24] , peripheral blood mononuclear cells [25] and neuroblastoma cell line SK-N-SH exposed to RF/MW at low SAR levels [5] . Howeer, Hsp expression has been reported to be upregulated by RF/electromagnetic field exposure in KB cells [26] , and levels of the inducible Hsp70C transcript were significantly enhanced after 24 h exposure to GSM signals in human trophoblast cells [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have focused on effect of non-thermal RF radiation in biological systems (Chauhan et al, 2007;Lee et al, 2006;Luukkonen et al, 2009;Qutob et al, 2006;Sanchez et al, 2007;Takashima et al, 2006;Verschaeve, 2009). Most of these studies have shown no significant effect on cellular and molecular levels in a variety of condition.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies have shown no significant effect on cellular and molecular levels in a variety of condition. Microarray analysis of gene expression showed that there is no evidence that non-thermal RF radiation affect gene expression in U87MG glioblastoma cells exposed to 1.9 GHz RF at SARs from 0.1 to 10 W/kg for 4 h and 24h, respectively (Chauhan et al, 2007;Qutob et al, 2006 reported that there were no effects of 1,800 MHz RF radiation at 2 W/kg SAR on HSP expression and apoptosis in human skin cells compare to ultraviolet (UV) and heat shock (Sanchez et al, 2007). In our previous studies, neither of cell cycle changes nor DNA damage as was detected in after 1,763 MHz RF exposure at an SAR of 10 W/kg SAR in Jurkat-T cells or 20 W/kg in auditory hair cells .…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that ionizing radiation, such as X-ray, affects biological systems, while it is still unclear and inconclusive whether non ionizing low-energy RF radiation could have effects on them. Although there have been a lot of studies of RF effects on biological systems for various aspects, most of them have focused on stress proteins, such as HSP, and MAPK signaling or DNA damages (Belyaev et al, 2006;Chauhan et al, 2006;Friedman et al, 2007;Lee et al, 2006;Sanchez et al, 2007;Sanchez et al, 2008, Verschaeve et al, 2009. For instance, Friedman et al (2007) found that exposure of HeLa and Rat1 cells to 875 MHz RF radiation induces the activation of the ERK cascade through ROS generation via NADH oxidase but not that of JNKs or p38 MAPKs.…”
Section: Introductionmentioning
confidence: 99%
“…If RF radiation exposure induces any biological effects in human, it must change cell behavior and gene expression (McNamee et al, 2009;Vanderstraeten et al, 2008). To date, some microarray analyses have been performed to elucidate the effects of RF radiation on biological systems (Chauhan et al, 2007;Lee et al, 2006;Lee et al, 2007;Paparini et al, 2009;Qutob et al, 2006;Sanchez et al, 2007;Zeng et al, 2006;Zhao et al, 2007). For example, non-thermal RF radiation did not affect gene expression in U87MG glioblastoma cells exposed to 1.9 GHz RF at SARs from 0.1 to 10 W/kg for 4 h and 24 h, respectively (Qutob et al, 2006;Chauhan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%